Alzheimer-type neuropathology in a 28 year old patient with iatrogenic Creutzfeldt-Jakob disease after dural grafting. Issue 3 (16th February 2006) - Preusser, M; Ströbel, T; Gelpi, E; Eiler, M; Broessner, G; Schmutzhard, E; Budka, H
Abstract : We report the case of a 28 year old man who had received a cadaverous dura mater graft after a traumatic open skull fracture with tearing of the dura at the age of 5 years. A clinical suspicion of Creutzfeldt-Jakob disease (CJD) was confirmed by a brain biopsy 5 months prior to death and by autopsy, thus warranting the diagnosis of iatrogenic CJD (iCJD) according to WHO criteria. Immunohistochemistry showed widespread cortical depositions of disease associated prion protein (PrP sc ) in a synaptic pattern, and western blot analysis identified PrP sc of type 2A according to Parchi et al . Surprisingly, we found Alzheimer-type senile plaques and cerebral amyloid angiopathy in widespread areas of the brain. Plaque-type and vascular amyloid was immunohistochemically identified as deposits of beta-A4 peptide. CERAD criteria for diagnosis of definite Alzheimer's disease (AD) were met in the absence of neurofibrillar tangles or alpha-synuclein immunoreactive inclusions. There was no family history of AD, CJD, or any other neurological disease, and genetic analysis showed no disease specific mutations of the prion protein, presenilin 1 and 2, or amyloid precursor protein genes. This case represents ( a ) the iCJD case with the longest incubation time after dural grafting reported so far, ( b ) the youngest documented patient with concomitant CJD and Alzheimer-type neuropathology to date, ( c ) the first description of Alzheimer-type changes in iCJD, and ( d ) the second case of iCJD in Austria. Despite the young patient age, the Alzheimer-type changes may be an incidental finding, possibly related to the childhood trauma.